Examining Academic Self-Efficacy and Perceived Social Support as Predictors for Coping With Stress in Peruvian University Students - Alfaro Vasquez, Rosa; Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Caycho-Rodríguez, Tomás (Frontiers in Education, 2022)
This study determines if academic self-efficacy and perceived social support are predictors for coping with stress in Peruvian university students. A cross-sectional research study of predictive design was employed. The study participants included 455 Peruvian university students. The global academic self-efficacy questionnaire, perceived social support survey, and academic stress coping scale were employed for the analysis. Further, the collected data were analyzed using correlation coefficients and multiple linear regression models. The study results revealed a statistically significant relationship between coping with stress, academic self-efficacy, and perceived social support. Linear regression analyses reported a satisfactory fit for the model (F-Test = 76.938, p < 0.001) wherein academic self-efficacy (β = 0.292, p < 0.05) and perceived social support (β = 0.360, p < 0.01) are variables that significantly predict stress-coping means used by the study participants (adjusted R2 = 0.25). Hence, it is evident that academic self-efficacy and perceived social support are predictors for coping with stress in Peruvian university students.